Biomimetic catalytic transformation of toxic α-oxoaldehydes to high-value chiral α-hydroxythioesters using artificial glyoxalase I - Sang Yeon Park; In-Soo Hwang; Hyun-Ju Lee; Choong Eui Song (Nature Communications, 2017)
Glyoxalase I converts toxic methylglyoxal to a thioester. Here the authors report a synthetic analogue capable of enantioselectively converting alpha-keto aldehydes to thioesters via formation of a hemithioacetal, giving access to both enantiomers of a range of alpha-hydroxy thioesters.